Review of fisheries and aquaculture policies in Ghana: technical report - Mapedza, Everisto D.; Buisson, Marie-Charlotte; Zane, Giulia; Appiah, Sarah; Asmah, R.; Ahiah, L.; Mensah, E. (International Water Management Institute (IWMI). CGIAR Initiative on Aquatic Foods, 2024)
This review report provides an overview of Ghana's fisheries and aquaculture sectors. The report summarizes and highlights the formal policies and governance structures related to aquaculture, inland fisheries, and marine fisheries in Ghana. The report identifies the legal frameworks and strategies governing these sectors and the plans and regulations in place. The aquaculture sector is an expanding subsector that has greater potential to increase and meet the increased demand for fish in Ghana, which is currently being met through imports.